The Use of Electrical Muscle Stimulation (EMS) as a Potential Intervention for Sarcopenia in older Adults - Mutiara, Karina; Sari, A A Indah Puspita; Sutanto, Kartika; Hadiningrat, D A A Diah; Marza, Amalia; Wahyuni, Nila; Adiatmika, I Putu Gede (Sport and Fitness Journal; Vol 10 No 2 (2022): Volume 10, No. 2, May 2022DO - 10.24843/spj.2022.v10.i02.p09, 2022)
As life expectancy increases and the population ages, effective interventions that promote long-term well-being and health are becoming increasingly important. Research results have proven that EMS can increase strength and muscle mass, so it is strongly suspected that EMS can be used to treat sarcopenia. This literature review summarizes various research results related to the use of electrical muscle stimulation (EMS) as a possible treatment for sarcopenia in older adults. From various scientific references used, it was found that EMS have a positive role with sarcopenia, especially in improving the function of skeletal muscle. Low-frequency stimulation appears to be more effective at strengthening, whereas high-frequency stimulation appears to favor muscle mass gain. EMS also promotes changes in muscle fiber composition as well as Enhanced oxidative enzymatic activity and glucose uptake. Moreover, EMS increases muscle strength, maintains overall muscle fiber size (which decreases with aging), activates satellite cells, and ensures muscle adaptation. We can also speculate that EMS mimics the effects of endurance training, does not cause muscle damage, and activates molecular tissues similarly to resistance training. All of this data could be used to create therapeutic strategies for aging-related sarcopenia.